...My Universe of woman... - Onã Silva (Universidad de Alicante, 2014)
The author uses the concatenation of different words with very different meanings to explicitly state a convergent sense, which confers them a common bond in the female cosmos: baby, midwife, mom, volunteer, virtuous, etc...This poetic activity underlies the subterranean identity of the caregiver as a woman.